2017
DOI: 10.1002/mds.26969
|View full text |Cite
|
Sign up to set email alerts
|

Prodromal spinocerebellar ataxia type 2: Prospects for early interventions and ethical challenges

Abstract: The characterization of prodromal stages in neurodegenerative disorders is becoming increasingly important because of the need for early neuroprotective therapies. Research during the past 3 decades in spinocerebellar ataxia type 2 has revealed a large body of evidence suggesting that many disease features precede the manifest cerebellar syndrome, which delineates the prodromal stage of this disorder. This stage is defined by clinical, imaging, and functional criteria, which are supported by early molecular ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 78 publications
2
23
0
Order By: Relevance
“…SCA2 is characterized by a progressive cerebellar syndrome accompanied by severe saccadic slowing, peripheral neuropathy, autonomic disturbances, pyramidal signs, cognitive disorders, and sleep disturbances . Similar to other SCAs caused by the polyglutamine domain, the onset of SCA2 cerebellar syndrome is significantly controlled by the mutation size and is preceded by prodromal manifestations up to more than a decade before disease onset …”
mentioning
confidence: 99%
“…SCA2 is characterized by a progressive cerebellar syndrome accompanied by severe saccadic slowing, peripheral neuropathy, autonomic disturbances, pyramidal signs, cognitive disorders, and sleep disturbances . Similar to other SCAs caused by the polyglutamine domain, the onset of SCA2 cerebellar syndrome is significantly controlled by the mutation size and is preceded by prodromal manifestations up to more than a decade before disease onset …”
mentioning
confidence: 99%
“…This phase is followed by the prodromal or preclinical stage, characterized by unspecific neurological features such as painful muscle cramps, sensory abnormalities, subtle cerebellar manifestation (increase of the sway during tandem gait), cognitive decline, autonomic disorders, olfactory dysfunction and hyperreflexia. Electrophysiological studies showed the reduction of the maximal saccadic velocity, REM sleep disorders, increased central motor conduction time in transcranial magnetic stimulation and peripheral sensory axonal damage according of the peripheral nerve conduction studies [3,24]. …”
Section: Lecture Highlightsmentioning
confidence: 99%
“…This discipline has emerged today from the research field as a mature and fully developed innovative research area that integrates not only pure topics of neuroimmunology, but also expands on wider fields such as neuroplasticity, neuronal reserve and neuromodulation. Several diseases were revised in interesting lectures to offer a major understanding of the molecular processes underlying neuroimmune pathology in neurodegenerative, neurodevelopmental and neurovascular diseases, as well as to understand some vulnerabilities occurring in these disorders [1,2,3,4,5]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations